An Insight into Ionic Conductivity of Polyaniline Thin Films - Chulkin, Pavel (Materials (Basel), 2020)
The work addresses an issue of the conductivity phenomenon in conductive polymer thin films. Polyaniline was chosen as a broadly used and thoroughly investigated conductive polymer in order to test and show capabilities of the developed original approach based on impedance spectra analysis. A number of films of different thickness were deposited onto a Pt electrode surface and consequently investigated in aqueous solution containing perchloric acid as an electrolyte. The processes that occur in polyaniline film were studied by cyclic voltammetry, electrochemical quartz crystal microgravimetry (EQCM) and electrochemical impedance spectroscopy (EIS). The role of incorporated ions as charge carriers was investigated with respect to the control of the conductivity properties of the film. Along with detailed polyaniline behavior study, the work makes up a fundamental scientific impact on theoretical electrochemistry and electroanalytical techniques.